2019
DOI: 10.1111/jphp.13086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new cyclic derivative of GABA, RGPU-207, on the functions of cardiac and cerebral mitochondria of stressed animals

Abstract: Objectives The objective of this study was to investigate the effects of a new derivative of GABA, RGPU-207 compound, on the mitochondrial functions of stressed animals. Methods RGPU-207 and the comparator drugs (phenibut and piracetam) were administered intraperitoneally to unstressed and stressed male rats at a dose of 9.4, 25 and 400 mg/kg, respectively. The oxygen consumption by cardiac and cerebral mitochondria in state 3 and 4 and Chance's respiratory control ratio (RCR) was investigated. The concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…GABA pretreatment also reduced ethanol‐induced gastric tissue and cells injury restraining oxidative stress by decreasing malondialdehyde level and increasing the activities of superoxide dismutase and catalase (Xie et al., 2017). In the study of mitochondria from stressed male rats treated with RGPU‐207, a cyclic derivative of GABA, the concentration of LPOs (malondialdehyde, conjugated dienes and diketones) in cardiac and brain mitochondria was lower than in the negative control (Mokrousov et al., 2019); however, in this last study the effects seemed to be rather centrally mediated. The results obtained in our study with stiripentol also suggest that the drug may have some inhibitory effect on LPO production in spermatozoa, which requires further studies focused predominantly on this aspect.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…GABA pretreatment also reduced ethanol‐induced gastric tissue and cells injury restraining oxidative stress by decreasing malondialdehyde level and increasing the activities of superoxide dismutase and catalase (Xie et al., 2017). In the study of mitochondria from stressed male rats treated with RGPU‐207, a cyclic derivative of GABA, the concentration of LPOs (malondialdehyde, conjugated dienes and diketones) in cardiac and brain mitochondria was lower than in the negative control (Mokrousov et al., 2019); however, in this last study the effects seemed to be rather centrally mediated. The results obtained in our study with stiripentol also suggest that the drug may have some inhibitory effect on LPO production in spermatozoa, which requires further studies focused predominantly on this aspect.…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that oxcarbazepine can also exert beneficial influence on the sperm parameters (Wu et al., 2018), whereas many other AEDs seem to be spermatotoxic (Asadi‐Pooya et al., 2015; Baysal et al., 2017; Hamed et al., 2015; Karaduman et al., 2019). It is well known that mitochondrial dysfunction leads to many changes within mitochondria and within mitochondrial membrane resulting first in so‐called mitoptosis and later to apoptosis (Mokrousov et al., 2019). However, in our study, the activity of mitochondria was the same in the control and the stiripentol‐treated group.…”
Section: Discussionmentioning
confidence: 99%